Transforming to university of Future (UoF): a conceptual model from the Somalian perspective - Yusuf Mohamed, Abdikadir; Ibrahim Hassan, Nuradin; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
The purpose of this paper is to propose a conceptual model to transform the current higher education in Somalia into the University of the Future (UoF). This paper will focused how to enhance the ICT in order to improve the level of higher education. However, the current problem of higher education in Somalia is the low ICT qualities especially the ICT infrastructure and the services that education sectors such as online platforms. In addition, the internet access in higher education causes another main problem of communication among students and lectures outside of class. This research will conduct a postal methodology and will distribute a questionnaire using the Business model canvas and Value Proposition Design frameworks were selected as the primary research instrument in order to gain a broad needs and demands for UoF, to a spectrum of universities in Somalia. From the questionnaires analysis and findings, this paper proposes a new business model canvas (BMC) and value proposition design (VPD) to implement the conceptual UoF model.